Baseline Assessment of 25-Hydroxyvitamin D Assay Performance: A Vitamin D Standardization Program (VDSP) Interlaboratory Comparison Study. (22nd November 2019) - Wise, Stephen A; Phinney, Karen W; Tai, Susan S-C; Camara, Johanna E; Myers, Gary L; Durazo-Arvizu, Ramon; Tian, Lu; Hoofnagle, Andrew N; Bachmann, Lorin M; Young, Ian S; Pettit, Juanita; Caldwell, Grahame; et al.
Abstract: The Vitamin D Standardization Program (VDSP) coordinated an interlaboratory study to assess the comparability of measurements of total 25-hydroxyvitamin D [25(OH)D] in human serum, which is the primary marker of vitamin D status. A set of 50 individual donor samples were analyzed by 15 different laboratoriesrepresenting national nutrition surveys, assay manufacturers, and clinical and/or research laboratories to provide results for total 25(OH)D using both immunoassays (IAs) and LC tandem MS (MS/MS). The resultswere evaluated relative to bias compared with the target values assigned based on a combination of measurements at Ghent University (Belgium) and the U.S. National Institute of Standards and Technology using reference measurement procedures for the determination of 25(OH)D2 and 25(OH)D3 . CV and mean bias for each laboratory and assay platform were assessed and compared with previously established VDSP performance criteria, namely CV ≤ 10% and mean bias ≤ 5%. Nearly all LC-MS/MS results achieved VDSP criteria, whereas only 50% of IAs met the criterion for a ≤10% CV and only three of eight IAs achieved the ≤5% bias. These results establish a benchmark for the evaluation of 25(OH)D assay performance and standardization activities in the future.